2015
DOI: 10.1038/leu.2015.31
|View full text |Cite
|
Sign up to set email alerts
|

Dinaciclib is a novel cyclin-dependent kinase inhibitor with significant clinical activity in relapsed and refractory chronic lymphocytic leukemia

Abstract: Dinaciclib (SCH727965) is a selective CDKi chosen for clinical development based upon a favorable therapeutic index in cancer xenograft models. We performed a phase I dose escalation study of dinaciclib in relapsed and refractory CLL patients with intact organ function and WBC < 200 × 109/L. Five separate dose levels (5 mg/m2, 7 mg/m2, 10 mg/m2, 14 mg/m2, and 17 mg/m2) were explored dosing on a weekly schedule × 3 with one week off (4 week cycles) using a standard 3+3 design with expansion cohorts to optimize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 36 publications
2
75
0
Order By: Relevance
“…BM cells were harvested from the femurs of BALB/c mice and cultured in complete RPMI containing mouse recombinant GMCSF (50 ng/ml) and IL-4 (25 ng/ml) (Peprotech) for 7 days to generate CD11c inated following a 2-hour i.v. infusion, with a terminal half-life of approximately 2 to 3 hours (41,58,74). In mice, the elimination of dinaciclib is even more rapid, with a half-life of less than 1 hour (48,58).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…BM cells were harvested from the femurs of BALB/c mice and cultured in complete RPMI containing mouse recombinant GMCSF (50 ng/ml) and IL-4 (25 ng/ml) (Peprotech) for 7 days to generate CD11c inated following a 2-hour i.v. infusion, with a terminal half-life of approximately 2 to 3 hours (41,58,74). In mice, the elimination of dinaciclib is even more rapid, with a half-life of less than 1 hour (48,58).…”
Section: Discussionmentioning
confidence: 98%
“…Here, we demonstrate that the CDK inhibitor dinaciclib (also known as MK-7965 and SCH727965) is capable of eliciting ICD. Dinaciclib is a potent CDK1, -2, -5, and -9 inhibitor that induces apoptosis in different tumor cells and has been shown to be clinically active in refractory chronic lymphocytic leukemia (38)(39)(40)(41)(42)(43)(44)(45)(46). These CDK targets regulate the cell cycle (CDK1, -2), control actin polymerization and neuronal function (CDK5), and regulate RNA-polymerase II (CDK9), and their repression can affect T cell proliferation and migration (47).…”
Section: Dinaciclib and Anti-pd1 Combination Therapy Inhibits Establimentioning
confidence: 99%
“…Structurally, this could be attributed to the large amount of shared features among the CDK family, particularly at the ATPbinding pocket, where current inhibitor discovery efforts are focused on. These structural similarities cause CDK9 Multiple clinical trials for hematologic and solid tumors (Parry et al 2010, Desai et al 2013, Flynn et al 2013, Nemunaitis et al 2013, Kumar et al 2015, Baker et al 2016 (Joshi et al 2007, Manohar et al 2011, Mishra et al 2013 www.clinicaltrials.gov…”
Section: Development Of Pharmacological Inhibitors Of Cdk9 For Pcamentioning
confidence: 99%
“…[7][8][9][10] Emerging novel agents provide substantial antileukemic effect with manageable toxicity and may represent attractive therapeutic strategies for older patients with ALL, either as components of initial therapy or as treatment at relapse. [11][12][13][14][15] There remains a paucity of data reflecting clinical outcomes in older US adults with ALL, particularly outside clinical trials, which provides historical context for evaluating novel approaches. Therefore, we used the National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) database to describe secular trends of median OS and long-term clinical outcome over the past 4 decades in US adults age $60 years with ALL.…”
Section: Org Frommentioning
confidence: 99%
“…13,14 A phase 1 study of dinaciclib in patients with CLL showed a partial response rate of ;63% in pretreated subjects at the recommended phase 2 dose (14 mg/m 2 ), 13 including responses in high-risk subgroups, such as patients with deletion of 17p (del17p). 13 Ofatumumab is a fully humanized type I anti-CD20 monoclonal antibody, 15,16 which binds to a different epitope of CD20 than rituximab.…”
mentioning
confidence: 99%